ASSESSING SPEAKING SKILLS THROUGH DIGITAL TOOLS - Ro'ziboyeva Binafsha Baxrom qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper examines the role of digital tools in assessing speaking skills in English as a Foreign Language (EFL) contexts. It focuses on the effectiveness, reliability, and pedagogical value of modern technological solutions such as speech recognition software, mobile applications, and online learning platforms. The study highlights how these tools provide immediate feedback, increase learner engagement, and support autonomous learning. At the same time, certain limitations, including technological constraints and the lack of human judgment, are critically discussed. The findings suggest that digital assessment, when combined with traditional methods, can significantly improve the quality and objectivity of speaking evaluation.